Service Quality and Customer Experience on Customer Satisfaction at Fast Food Restaurants in Medan City - Atika Aini Nasution; Aan Nurhadi; M. Asyari Syahab (Proceeding of The International Conference on Business and Economics, 2024)
Factors that can attract consumer interest in satisfying customers at fast food restaurants in Medan City include providing quality service. In addition to service quality, customer experience is also another factor that can attract consumer interest in buying. One thing that companies can do is to build a brand so that it will create brand equity. Based on the description above, the title of the study is, " The Effect of Service Quality and Customer Experience on Customer Satisfaction at Fast Food Restaurants in Medan City ". The purpose of this study is to determine the effect of service quality and customer experience on customer satisfaction at fast food restaurants in Medan City, both partially and simultaneously, and the formulation of the problem in this study is whether service quality and customer experience affect customer satisfaction at fast food restaurants in Medan City. The results of the study indicate that service quality has a significant effect on customer satisfaction , customer experience has a significant effect on customer satisfaction and simultaneously the variables of service quality and customer experience have a significant effect on customer satisfaction. The company should pay more attention to the quality of service that has been provided to users of delivery services so that the service is not just a slogan but is implemented seriously so that the company's image is maintained in the eyes of service users.